Analysis on the Corrosion Causes of Hot-Dip Galvanizing Heat Exchange Tube - CHEN Jie-ming, YANG Xiao, GUO Hai-xia, YUAN Xiao-dong, LI Xue-feng (Cailiao Baohu)
The corrosion leakage of the hot-dip galvanizing heat exchange tube of 15CrMo occurred after about 2 a of use.The failure reason was analyzed by metallographic analysis,chemical composition analysis,scanning electron microscope,energy dispersive spectrometry,X ray diffraction,combined with the field service conditions and environment of the failed parts.Results showed that the reasons for corrosion and leakage of hot-dip galvanizing tube were the higher concentration of corrosive ions Cl-and SO 2-4 in the external spray cooling water,which accelerated the corrosion of the zinc coating.At the same time,the zinc coating quality problem(micro cracks and many coarse columnar crystalsζPhase)reduced its corrosion resistance.Besides,the high temperature environment increased the corrosion rate of the zinc coating,resulting in the corrosion damage of the zinc coating,the loss of its protective effect,and the corrosion leakage of the pipe substrate.